If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 4y + -9(8x + -7y + 22) = 0 Reorder the terms: 8x + 4y + -9(22 + 8x + -7y) = 0 8x + 4y + (22 * -9 + 8x * -9 + -7y * -9) = 0 8x + 4y + (-198 + -72x + 63y) = 0 Reorder the terms: -198 + 8x + -72x + 4y + 63y = 0 Combine like terms: 8x + -72x = -64x -198 + -64x + 4y + 63y = 0 Combine like terms: 4y + 63y = 67y -198 + -64x + 67y = 0 Solving -198 + -64x + 67y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '198' to each side of the equation. -198 + -64x + 198 + 67y = 0 + 198 Reorder the terms: -198 + 198 + -64x + 67y = 0 + 198 Combine like terms: -198 + 198 = 0 0 + -64x + 67y = 0 + 198 -64x + 67y = 0 + 198 Combine like terms: 0 + 198 = 198 -64x + 67y = 198 Add '-67y' to each side of the equation. -64x + 67y + -67y = 198 + -67y Combine like terms: 67y + -67y = 0 -64x + 0 = 198 + -67y -64x = 198 + -67y Divide each side by '-64'. x = -3.09375 + 1.046875y Simplifying x = -3.09375 + 1.046875y
| 4(x-8)=-12 | | 8-8(8n+6)=-8(5n+1)-2 | | m+m-2+m=-4+11 | | 79=9c-2 | | -5x+5=16 | | 19f+23-7f=145+(-14) | | 2e-8=10 | | 6p=36 | | -v-8v=6+3 | | 4p+28-3p=77-28 | | 8(x-8)=-32 | | 9/(6)89=121 | | 8(a+5)=88 | | x+40=5-6x | | -6x+1=-5 | | x+(2x)+(3x+2)=122 | | 15=9c-3 | | 275=7r-47+7r | | -15=5(3a-10)-5q | | x+5x=216 | | 6u+14=-19 | | 50-(4x+5x)=32 | | 6w-1=-13 | | 7k-36+3k=84 | | -9+(-2)= | | 99c-23/6=37 | | 3(4x+1)=9-5(4x-3) | | 26=5a+11 | | 10y=4y+3+5y | | 3y-y+7y=173+(-29) | | 6.5x+8.45=3.3x | | 9m+6=105 |